Enzymes in Farm Animal Nutrition (2nd Edition) - Bedford, Michael R (CABI, 2014)
There have been considerable developments in the feed enzyme industry since the ﬁ rst edition of this book was published in 2001, both in terms of the size and scope of the commercial market and in our scientiﬁ c understanding of how feed enzymes function. With such rapid changes it became clear that much of the information in the ﬁ rst edition of this book needed to be updated. The reader is referred back to the ﬁ rst edition for a foundation in the fundamentals of the market and science, whereas this edition is more focused on changes in the interim. Most notable is the rapid expansion of both the phytase and non-starch polysaccharide (NSP) enzyme segments. Today, the total feed enzyme market is approximately four times larger in value terms than it was in the early 2000s, but the split in species applications remains broadly similar. Sales are highest in poultry, followed by swine, with the ruminant market in its infancy. Aquatic and pet applications have yet to become commonplace. Penetration of phytase into the poultry and swine sectors is relatively high, while the NSP enzyme market still has some considerable growth potential, particularly in swine. Much of the expansion of the market has been driven by reduced inclusion costs of feed enzymes, which was predicted in the ﬁ rst edition, and signiﬁ cant volatility in feed ingredient prices, which was not. The latter drove many feed manufacturers to seek methods, such as enzymes, to maximize utilization of less costly raw feed materials as the prices of maize, soy, fat and mineral phosphates soared in late 2007.